Kualitas Semen Beku Sapi Limousin pada Permukaan Nitrogen Cair dengan Jarak yang Berbeda Pasca Thawing - Hoesni, Fachroerrozi; Farizal, Farizal; Firmansyah, Firmansyah; Afzalani, Afzalani; Muthia, Tata (Jurnal Ilmiah Universitas Batanghari Jambi, 2026)
This study was conducted to evaluate the quality of frozen Limousin cattle semen after thawing, placed on a liquid nitrogen surface with varying distances. The method used was a Completely Randomized Design (CRD) consisting of 6 treatments and 5 replications. The treatments included P0 as a control (the straw remained immersed in liquid nitrogen), P1 (the straw was raised 5 cm above the liquid N₂ surface), P2 (10 cm), P3 (15 cm), P4 (20 cm), and P5 (25 cm). The study lasted for one month, from October 27, 2023, to November 27, 2023, and was conducted at the Laboratory of the Food Crops, Horticulture, and Animal Husbandry Service of Jambi Province. The parameters observed included motility, viability, and spermatozoa abnormalities. The data obtained were analyzed using analysis of variance (ANOVA), and if it showed a significant effect, it was continued with the Duncan Test. The results showed that placing frozen Limousin cattle semen on a liquid nitrogen surface affected sperm motility and viability, but did not affect the level of abnormalities. A decrease in motility and viability was observed in treatments P4 and P5. Therefore, it can be concluded that placing frozen Limousin cattle semen at a height of 15 cm above the liquid nitrogen surface for 30 seconds can still maintain sperm quality.